FOREIGN EXECUTIVES IN THAI ORGANIZATIONS: AN EXPLORATION OF DIVERSITY AND HOW INNOVATION WILL HELP - Thepmongkorn, Sirintorn; Srisangkhajorn, Thaksaorn; Johnson, James Vincent (PEOPLE: International Journal of Social Sciences, 2015)
In today's global society, a large number of Thai people, working in Thailand, are managed by expats from western cultures. The resulting management challenges exist in all offices in Thailand that are managed by expats, both foreign companies and Thai companies. Many expat managers are not familiar with Thai cultural norms, but due to the Asean Economic Community, Thailand is becoming more open to foreign investment, including foreign companies establishing operations within Thailand. Overcoming cross-cultural misunderstandings will enable expat managers and Thai staff to communicate more successfully, and thus achieve their business purposes. Although all expat managers should receive appropriate cultural training before beginning their management assignment in Thailand, it is unclear how many managers actually receive specialized training, or how effective the training is. Because cross-cultural encounters are unavoidable when communicating in an international setting, all managers should use innovative management techniques to address cultural challenges. Once again, it is not clear how many managers actually use effective techniques. The level of technological and non-technological innovation may reflect the level of organizational innovation management employed by the company. Without the use of innovative techniques, managers will struggle to handle the unique challenges of managing a Thai staff. This paper provides some preliminary information on the types of problems that expat managers must address on a regular basis, problems such as culture shock, diversity in communication styles, hierarchy in Thai organizations, and how expats perform innovation employee management. The research goal of this study is to determine which innovation techniques are similar among the target companies, which companies employ different or unusual innovation techniques, and which companies do not use any of the well-known innovation techniques.